Front Cover: Anti‐SARS‐CoV‐2 Inhibitory Profile of New Quinoline Compounds in Cell Culture‐Based Infection Models (Chem. Eur. J. 4/2022). Issue 4 (12th January 2022) - Herrmann, Lars; Hahn, Friedrich; Wangen, Christina; Marschall, Manfred; Tsogoeva, Svetlana B.
Abstract : A new anti‐SARS‐CoV‐2 compound, developed in this joint study, is shown in front of SARS‐CoV‐2 viruses. The ongoing pandemic of human SARS‐CoV‐2 infections (COVID‐19) creates a high demand for antiviral drug development. The shown quinoline–morpholine hybrid and other new quinoline‐based compounds were synthesized and investigated for their in vitro activity against SARS‐CoV‐2. They exerted an anti‐SARS‐CoV‐2 activity similar to or stronger than that of the reference drug. More information can be found in the Research Article by M. Marschall, S. B. Tsogoeva et al. (DOI: 10.1002/chem.202103861 ).